Does relational leadership generate organizational social capital? A case of exploring the effect of relational leadership on organizational social capital in China - Tayyaba Akram; Shen Lei; Syed Talib Hussain; Muhammad Jamal Haider; Muhammad Waqar Akram (Future Business Journal, 2016)
The aim of this study was to investigate the effect of relational leadership on organizational social capital. Three forms of organizational social capital namely structural, relational and cognitive organizational social capital are used as dependent variables. Using self- administered questionnaire, Data of 240 employees was collected from an IT company in China. Data was analyzed using correlation and multiple regression analysis. Results of this study suggested that relational leadership plays a positive and significant role in generating structural and relational organizational social capital. However, this study failed in finding the effect of relational leadership on cognitive organizational social capital. Practical implications and limitations are also provided at the end.
Keywords: 650; China; Cognitive organizational social capital; Relational leadership; Relational organizational social capital; Structural organizational social capital